AB0395 Correlation between cardiovascular risk calculators in a cohort of patients with rheumatoid arthritis. (12th June 2018) - Castellanos-Moreira, R.; Rodriguez-Garcia, S.C.; Mandelikova, S.; Ruiz-Esquide, V.; Frade-Sosa, B.; Azuaga-Piñango, A.B.; Rodriguez-Garcia, S.D.C.; Sapena, N.; Gonzalez-Delaurens, C.; Camacho, O.; Ramírez, J.; Hernández, M.V.; et al.
Abstract : Background: EULAR recommends for patients with rheumatoid arthritis (RA) a cardiovascular (CV) risk assessment at least once every five years. Several risk calculators are available but most of them are based on data from general population, so they may underestimate the risk of RA patients. To obtain a more accurate estimation they should be adapted for RA by a 1.5 multiplication factor, unless the instrument includes RA as a variable. To date, there are no studies analysing the concordance and correlation between different CV risk calculators in spanish population. Objectives: To analyse concordance and correlation of CV risk calculated using different tools and to determine the proportion of CV risk factors in a cohort of patients with RA. Methods: We performed a cross-sectional study including patients with RA according to ACR/EULAR 2010 criteria, treated in a tertiary hospital. Individuals with previous CV events, diabetes and chronic kidney disease were excluded. Ten-year CV risk was obtained with the following calculators: Framingham-body mass index (FRS-BMI), Framingham-lipids (FRS-L), SCORE CV risk calculator (SCORE) and the Expanded CV Risk Prediction Score for RA (ERS-RA). A 1.5 multiplying factor was used to adapt the results for RA patients in those which didn't include it in their models. CV risk was categorised as low or high using 10% as a cut-off for FRS-BMI and FRS-L and 5% for SCORE y ERS-RA. Correlation was evaluated using Spearman correlation coefficient (Rho) and concordance with weighted kappa. Results: We included 88 patients (1 8 male), 87.5% Caucasian, mean age 56.9±10.6 years, mean disease duration 5.8±3.3 years. 67% and 76% had positive RF and ACPA respectively and 15% presented extra-articular manifestations (rheumatoid nodules, interstitial lung disease, pleuropericarditis). Regarding CV risk factors: 14.8% were active smokers, 60.2% were overweight or obese, 25% had hypertension, 47.8% had dyslipidemia. The median CV risk predicted at 10 years was 15% (1.5–70.20) for FRS-IMC, 11.8% (1.2–54.0) for FRS-L, 1.5% (1.1–16.5) for SCORE and 6% (0.6–27.8) for ERS-AR. 64 patients were categorised as low risk and 22 as high risk for ERS-AR. No significant differences were observed in the means of risk obtained by the different calculators or in the risk categories according to ERS-RA when stratified by disease duration (more or less than 5 years). For the correlation between ERS-RA and FRS-BMI, FRS-L and SCORE, Spearman's Rho coefficients were 0.84, 0.79 and 0.80. (p<0.005). For the concordance between ERS-RA vs FRS-BMI a weighted κ=0.29 (CI95 0.15–0.42) was obtained. For ERS-AR vs FRS-L, κ=0.34 (CI95 : 0.19–0.50) and for ERS-AR vs SCORE, κ=0.70 (CI95 : 0.52–0.87). Conclusions: A strong correlation was observed between the CV risk calculators evaluated and good agreement only between ERS-AR and SCORE. Additionally, overweight, obesity and dyslipidemia were the most prevalent comorbidities. Disclosure of Interest: None declared